Argentina : First Review under the Stand-By Arrangement; Inflation Consultation; Financing Assurances Review; and Request for Rephasing, Augmentation, Waivers of Nonobservance and Applicability of Performance Criteria, and Modification of Performance Criteria-Press Release; Staff Report; and Staff Supplement. (IMF Staff Country Reports; Country Report, 2018)
This paper discusses Argentina's First Review Under the Stand-By Arrangement (SBA), Inflation Consultation, Financing Assurances Review, and Requests for Rephasing, Augmentation, Waivers of Nonobservance and Applicability of Performance Criteria. All performance criteria and the structural benchmark for end-June were met. The authorities have proactively recognized that restoring stability in Argentina will require a significant reshaping of their policy program and have requested changes in the nature of IMF support under the SBA. The authorities are forcefully strengthening their policy program by eliminating the primary fiscal deficit in 2019 and targeting a primary surplus in 2020. The IMF staff supports the authorities' request to modify the program supported by the SBA.